Kiwi Entrepreneurs A Study - Gilbertson, D.K; Wright, H; Yska, G; Gilbertson, D.W (School of Management Working Papers, 1995)
Entrepreneurship and innovation are important cornerstones of competitive advantage. This paper explores the nature of entrepreneurs in New ’Zealand It looks at the factors that have enabled them to become entrepreneurs, what else would have helped them to be successful or caused failure, their trials and how they overcame them, and in retrospect what they would have done differently. One hundred and twenty-eight in-depth, personal interviews were conducted of entrepreneurs. Most of the interviewees had some experience of using government agencies who had offered training, support and financial assistance. This research highlights the lessons that entrepreneurs have learnt about what it takes to be successful at setting up a new business ( entrepreneurship) and developing new ideas (innovation). It also provides insights into the way government agencies can tailor their assistance to more effectively promote entrepreneurship.